Subconjunctival Myolipoma Confirmed with Immunohistochemical Analysis: A Case Report - Asadi-Amoli, Fahimeh; Soleimani, Mohammad; Nozarian, Zohreh; Garebaghi , Reza; Ghazanfari , Tooba; Parvizi, Maryam; Rezaei, Keivan; Tabatabaei , Seyed Ali (Journal of Ophthalmic and Optometric Sciences, 2019)
Purpose: To report the clinicopathological features of a rare case of subconjunctival myolipoma and its treatment results. Case Report: A 17-year-old female patient referred to our center with a white-pink mass in her left upper bulbar conjunctiva. The lesion extended to the forniceal conjunctiva. The patient had otherwise normal complete ocular examinations and underwent complete surgical excision of the mass due to cosmetic concerns. The tumor was examined with light–microscopy, following hematoxylin and eosin (H&E), Masson-trichrome, and immunohistochemical (IHC) staining.A definite diagnosis of subconjunctival myolipoma was acheived following the pathological assessment. Six months postoperatively, no tumor recurrence was noted, and ocular examinations were within normal limits.